Does conditioned pain modulation predict the magnitude of placebo effects in patients with neuropathic pain?. (20th December 2017) - Skyt, I.; Moslemi, K.; Baastrup, C.; Grosen, K.; Svensson, P.; Jensen, T.S.; Vase, L.
Abstract: Background: Conditioned pain modulation (CPM) is a validated measure of the function of endogenous pain inhibitory pathways. Placebo effects reflect top‐down inhibitory modulation of pain. CPM and placebo effects are both influenced by expectations, albeit to varying degrees, and are related to neurotransmitter systems such as the endogenous opioid system, and it can be speculated that CPM responses are positively associated with the magnitude of placebo effects. Yet, no studies have tested this. Methods: The study included 19 patients with neuropathic pain. CPM was quantified as the difference in pressure pain threshold (PPT) as measured at the middle deltoid muscle before and after 5‐min exposure to the cold pressor test (CPT) (conditioning pain stimulus). Placebo effects were tested via open and hidden applications of the pain‐relieving agent lidocaine (2 mL) using a disinfection napkin controlled for no treatment. Results: The mean (SD) PPT was 668.7 (295.7) kPa before and 742.3 (370.8) kPa after the CPT. The mean (SD) CPM response was −73.6 (214.0) kPa corresponding to an 11% increase in PPT, reflecting a normally functioning endogenous pain modulatory system. Large and significant placebo effects were observed in ongoing neuropathic pain intensity ( p = 0.002). The CPM response did not predict the magnitude of the placebo effect ( p = 0.765). Moreover, there were no interaction effects for the moderator variables: clinical pain level ( p = 0.136), age ( p = 0.347) and gender ( p = 0.691). Conclusions: Conditioned pain modulation and placebo effects do not seem to be associated in patients with neuropathic pain. Significance: Conditioned pain modulation and placebo effects are endogenous pain‐modulating phenomena that are influenced by some of the same mechanisms. This study suggests that CPM and placebo effects in neuropathic pain are independent phenomena that may be mediated by different mechanisms.